EFEKTIVITAS EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) DI MADRASAH ALIYAH NEGERI 5 SLEMAN - Wahir Tupono (Universitas Muhammadiyah Bengkulu, 2020)
Abstract: Education Management Information System (EMIS) at MAN 5 Sleman is a one-door online madrasah data collection but in reality there are still often problems such as the National Student Registration Number (NISN) is not appropriate, NISN is not found and there is student data that is not found / lost in the application EMIS. This has resulted in its own constraints in managing EMIS data at MAN 5 Sleman. The purpose of this study was to determine the effectiveness of EMIS in MAN 5 Sleman and the effect on the success of students taking the National Computer Based Test (UNBK). The benefit of this research is that the wider community knows that MAN 5 Sleman in data management has used an online system called EMIS, so that data that is at MAN 5 Sleman can be accessed anytime and anywhere. This type of research uses descriptive qualitative methods, while the data collection techniques use interviews, observation and documentation with the data validity test by means of triangulation